Avaliação do efeito do adoçante artificial aspartame, sobre moscas Drosophila melanogaster, modelo da cascata ß-amilóide - Carvalho, Alice Norberto de (2021)
Alzheimer's disease (AD) is characterized by progressive and irreversible loss of neural tissue, which is why it is defined as a neurodegenerative disease. In its two forms of manifestation; sporadic Alzheimer’s disease (SAD/LOAD) and familial Alzheimer’s disease (FAD), patients have cognitive, physiological and behavioral dysfunctions, memory loss and dementia. AD is the most common form of dementia, accounting for 75% of all cases. The diagnosis depends on the identification of classic pathological marks, which are senile plaques and neurofibrillary tangles. Considering ß-amyloid plaques as one of the signs of the disease, Drosophila melanogaster flies, model of the ß-amyloid pathway, were used to evaluate the effect of the artificial sweetener aspartame (ASP) on AD, since aspartic acid and phenylalanine, both byproducts of ASP hydrolysis, have been described as neurotoxic agents, but rarely correlated, specifically, with Alzheimer's. Using Drosophila as an experimental model, it was possible to assess whether the consumption of this sweetener raised the fluorescence of amyloid proteins in the fly's brain, and whether this increase correlated with a motor decline. In addition, cerebral glucose was measured after consumption of the drug. Our results suggest a relationship, albeit weak, between the consumption of ASP and AD in flies. Considering that the sweetener currently has an indiscriminate use, and that the increase in life expectancy of the world population is associated with the increase in the number of cases of the disease, further studies between ASP and AD are needed, for a definitive correlation.